2009
DOI: 10.1111/j.1348-0421.2009.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the distribution patterns of BK polyomavirus lineages among China, Korea and Japan: Implications for human migrations in northeast Asia

Abstract: BKV is widespread among humans, infecting children asymptomatically and then persisting in renal tissue. Based on the serological or phylogenetic method, BKV isolates worldwide are classified into four subtypes (I-IV), with subtypes I and IV further divided into several genetically-distinct subgroups. Since, similarly to JCV, a close relationship exists between BKV lineages and human populations, BKV should be useful as a marker to trace human migrations. To elucidate ancient human migrations in northeast Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…In addition, based on the SNP analysis, the major subtype I subgroup (Ic) was classified into two subdivisions, Ic/Ch and Ic/KJ. Zhong et al [28] found that Korea and Japan shared two features in the distribution of BKV lineages. First, a subdivision (Ic/KJ) of subgroup Ic was mainly detected in Korea and Japan, whereas another subdivision (Ic/Ch) occurred predominantly in China; and second, of the various subtype IV subgroups, IVb2 occurred predominantly or at the highest rate in Korea and Japan, and rarely in China.…”
Section: Japanese Ancestors (The Yayoi Immigrants) Came Through the Kmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, based on the SNP analysis, the major subtype I subgroup (Ic) was classified into two subdivisions, Ic/Ch and Ic/KJ. Zhong et al [28] found that Korea and Japan shared two features in the distribution of BKV lineages. First, a subdivision (Ic/KJ) of subgroup Ic was mainly detected in Korea and Japan, whereas another subdivision (Ic/Ch) occurred predominantly in China; and second, of the various subtype IV subgroups, IVb2 occurred predominantly or at the highest rate in Korea and Japan, and rarely in China.…”
Section: Japanese Ancestors (The Yayoi Immigrants) Came Through the Kmentioning
confidence: 99%
“…In 1993, Jin et al [10] PCR-amplified and sequenced a 287-bp VP1 region (also designated as the 287-bp typing region, and referred to as TR in Figure 1) of the BKV genome that contained a possible epitope region responsible for serological discrimination among subtypes, and the resultant sequences were used to detect subtype-specific single-nucleotide polymorphisms (SNPs). The sequence variation within this region has since been used to classify BKV strains in various laboratories [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], and the results of these studies showed the following distribution pattern for BKV subtypes. Subtype I is widespread in the world, subtype IV shows a geographic distribution that is biased towards East Asia and Europe and subtypes II and III are rarely detected worldwide.…”
Section: Genomic Subtypes Of Bkvmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the incidence of BKV in the urine of immunocompetent individuals in the Korean population has been reported [35]. 35% of the examined immunocompetent individuals were BKV-positive.…”
Section: Discussionmentioning
confidence: 99%